Prophylactic intra-peritoneal drain placement following pancreaticoduodenectomy: a systematic review and meta-analysis - Wang, Yi-Chao; Szatmary, Peter; Zhu, Jing-Qiang; Xiong, Jun-Jie; Huang, Wei; Gomatos, Ilias; Nunes, Quentin M; Sutton, Robert; Liu, Xu-Bao (World journal of gastroenterology : WJG, 2015)
To conduct a meta-analysis comparing outcomes after pancreaticoduodenectomy (PD) with or without prophylactic drainage. Relevant comparative randomized and non-randomized studies were systemically searched based on specific inclusion and exclusion criteria. Postoperative outcomes were compared between patients with and those without routine drainage. Pooled odds ratios (OR) with 95%CI were calculated using either fixed effects or random effects models. One randomized controlled trial and four non-randomized comparative studies recruiting 1728 patients were analyzed. Patients without prophylactic drainage after PD had significantly higher mortality (OR=2.32, 95%CI: 1.11-4.85; P=0.02), despite the fact that they were associated with fewer overall complications (OR=0.62, 95%CI: 0.48-0.82; P=0.00), major complications (OR=0.75, 95%CI: 0.60-0.93; P=0.01) and readmissions (OR=0.77, 95%CI: 0.60-0.98; P=0.04). There were no significant differences in the rates of pancreatic fistula, intra-abdominal abscesses, postpancreatectomy hemorrhage, biliary fistula, delayed gastric emptying, reoperation or radiologic-guided drains between the two groups. Indiscriminate abandonment of intra-abdominal drainage following PD is associated with greater mortality, but lower complication rates. Future randomized trials should compare routine vs selective drainage.